2015
DOI: 10.1111/febs.13536
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and structure‐based prediction of fructosyltransferase activity for functional subclassification of fungal GH32 enzymes

Abstract: Sucrolytic enzymes catalyse sucrose hydrolysis or the synthesis of fructooligosaccharides (FOSs), a prebiotic in human and animal nutrition. FOS synthesis capacity differs between sucrolytic enzymes. Amino-acidsequence-based classification of FOS synthesizing enzymes would greatly facilitate the in silico identification of novel catalysts, as large amounts of sequence data lie untapped. The development of a bioinformatics tool to rapidly distinguish between high-level FOSs synthesizing predominantly sucrose hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…The GH32A group includes enzymes that have been biochemically characterized as having levanase/inulinase activities, [ 28,29 ] while the GH32B group includes enzymes described as having sucrase activity. [ 30 ] HGT of bacterial GH32 has been previously described in Bomby mori [ 31 ] and in Sphenophorus levis . [ 32 ] This atypical adaptive evolution for the efficient digestion of plant‐specific fructans appears to have occurred in multiple species in a punctuated manner, except for the sucrase (GH32B) HGT in Lepidoptera, which apparently occurred in an early evolutionary lineage of Lepidoptera and subsequently was maintained in multiple lepidopteran species (Figure 1C, and Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The GH32A group includes enzymes that have been biochemically characterized as having levanase/inulinase activities, [ 28,29 ] while the GH32B group includes enzymes described as having sucrase activity. [ 30 ] HGT of bacterial GH32 has been previously described in Bomby mori [ 31 ] and in Sphenophorus levis . [ 32 ] This atypical adaptive evolution for the efficient digestion of plant‐specific fructans appears to have occurred in multiple species in a punctuated manner, except for the sucrase (GH32B) HGT in Lepidoptera, which apparently occurred in an early evolutionary lineage of Lepidoptera and subsequently was maintained in multiple lepidopteran species (Figure 1C, and Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…These microbes lack specific levanases. Many different fungi employ various GH32 family hydrolases (Trollope, Wyk, Kotjomela, & Volschenk, ; Van der Nest et al, ); however, there have been no reports on fungal GH68 enzymes. 3D structures of two different fungal inulinases from Aspergillus amawori (PDB ID: 1Y4W) and Aspergillus ficuum ( PDB ID: 3RWK); and invertases / β‐fructofuranosidases from Schwanniomyces occidentalis (PDB ID: 3KF5), Aspergillus kawachii (PDB ID: 5XH9), Saccharomyces cerevisiae (PDB ID: 4EQV), and Xanthophyllomyces dendrorhous (PDB ID: 5ANN) have been obtained so far.…”
Section: Fructans and The Gh‐j Clan Enzymesmentioning
confidence: 99%
“…11) However, the yeast FFases such as SoF-Fase has also transfructosylation activity, 46) and a mutagenesis study of two underlined residues in the WMNDPNG motif (Trp47 and Asn49 in SoFFase) suggested that the motif is involved in hydrolase/transferase activity. 11,47) In addition, two Trp residues (Trp76 and Trp314 in SoFFase) form the catalytic cleft of yeast FFases along with the Asn and Trp residues ( Fig. 6(A)).…”
Section: Insights Into the Transfructosylation Of Akffasementioning
confidence: 99%
“…In contrast, FFases that exhibit a weak ability to produce FOS, such as Aureobasidium pullulans FFase, have been found. 11) A combination of alignment and structural analyses of GH32 enzymes indicated that lowlevel FOS-producing enzymes contain a WMNDPNG motif, while high-level FOS-producing enzymes contain a GQIGDPC motif. 11) Aspergillus kawachii IFO 4308 is a filamentous fungus that is used to brew alcoholic beverages.…”
mentioning
confidence: 99%
See 1 more Smart Citation